Treasure chest of six sigma growth methods, tools, and best practices : a desk reference book for innovation and growth - Hambleton, Lynne (Prentice Hall Six Sigma for innovation and growth series., 2007)
"This reference is the first comprehensive how-to collection of Six Sigma tools, methodologies, and best practices. Leading implementer Lynne Hambleton covers the entire Six Sigma toolset, including more than 70 different tools - ranging from rigorous statistical and quantitative tools to "softer" techniques. The toolset is organized in an easy-to-use, alphabetical encyclopedia and helps professionals quickly select the right tool at the right time for every business challenge, taking the fear out of the selection process and proper application." "Hambleton systematically discusses which questions each tool is designed to answer; how the tool compares with similar tools; when to use it; how to use it step-by-step; how to analyze and apply the output; and which other tools it complements. To further illustrate and clarify tool usage, she presents hundreds of figures, along with never-before-published hints, tips, and real-world, "out-of-the-box" examples."--Jacket